(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: With advent of crime recorded by the perpetrator of a young age, accurate age estimation is important to determine the further course of action, beyond this it even helps to determine, disaster victim identification (DVI), sports, fashion, education and many more. Several studies and formula have been proposed over the years for various parts of the world and amongst them Cameriere’s method is now being accepted globally, and the related work is still one of the most thought about. Aim: The overall purpose of conducting the research is to correlate chronological age(CA) with Cameriere third molar maturity index(I3M) and to compare chronological age (CA) with Demirjian 10 stage age estimation method and also to determine which amongst the two will be a